Super sprint triathlon performance progression in young state and national standard Australian triathletes - Correa, G. S.; Lorimer, A.; Rathbone, E.; Eastwood, A.; Keogh, J. (International Journal of Performance Analysis in Sport, 2024)
Adolescent sports performance is multifaceted. Investigation of the performance trajectory of young state- and national-standard triathletes may provide valuable information on athlete development. A total of 412 Super Sprint triathlon results were modelled using linear mixed effects to generate performance trajectories as athletes aged with athlete and competition as random effects. Velocity trajectories were estimated for full race, swim, cycle and run segments. Estimated 13-year-old full-race velocity is 5.97 (95% CI: 5.57, 6.37) m·s-1 for males and 5.66 (95% CI: 5.31, 6.01) m·s-1 for females. Swim, cycle and run velocities are 1.11 (95% CI: 1.08, 1.14); 8.50 (95% CI: 7.97, 9.01); and 4.47 (95% CI: 4.37, 4.57) m·s-1 for males and 1.10 (95% CI: 1.08, 1.13); 8.03 (95% CI: 7.58, 8.50); and 4.11 (95% CI: 3.94, 4.27) m·s-1 for females. Yearly improvements in full-race and cycling reduce with age for males and females, due to the negative quadratic trend which is not present for both sexes swimming and for males running. Females did not show a statistically significant improvement with age in the run segment. Our results support previous research on adolescent swimming while providing new insights for cycling and female running.